Directly induced hepatogenic cells derived from human fibroblast ameliorate liver fibrosis. (26th June 2020) - Choi, Ja Sung; Han, Seongho; Ryu, Hyun Aae; Kim, Sung‐Whan
Abstract: Recently, reprogramming technology has emerged as a fascinating tool to generate specific tissue cells. In this study, we tested the hypothesis that ultrasound‐directed cellular reprogramming can generate fibroblasts into hepatogenic cells. We directly induced human dermal fibroblasts (HDFs) into hepatocyte‐like cells mediated by environmental transition‐guided cellular reprogramming (h/entr) using ultrasound. We confirmed the characteristics of h/entr by the expression levels of hepatocyte specific RNA and proteins. The effects of h/entr on the activation of hepatic stellate cells were analyzed using conditioned medium (CM). h/entr were transplanted into mice with acute liver fibrosis and the therapeutic effects and mechanism of liver fibrosis were determined. h/entr exhibited high levels of hepatocyte specific genes, hepatogenic (hepatocyte growth factor [HGF], colony‐stimulating factor 3 [CSF‐3]) and anti‐inflammatory (interleukin 10 [IL‐10]) factors. h/entr CM suppressed the activation of hepatic stellate cells in vitro. Transplantation of h/entr significantly delayed liver fibrosis and improved liver function. Transplantation of h/entr accelerates liver regeneration, and human albumin expressing h/entr and human Alu gene were detected in the mouse livers. This report suggests that directly induced h/entr could be one of the highly effective therapeutic options for the treatment of liver cirrhotic disease.